Matthew's Judaization of Mark : examined in the context of the use of sources in Graeco-Roman antiquity - O'Leary, Anne M. (Library of New Testament studies ;, 2006)
Creative imitation (Gk., mimesis; Lt., imitatio) was the primary literary convention of the ancient world of the first century CE. In the first part of the book it is demonstrated that it was the principal means by which classical authors, for example, Virgil, Seneca, Plutarch, and Livy, composed their works. An examination of the use of sources in both Jewish and Christian Sacred Scriptures in the light of this convention provides a new and fruitful approach to scripture scholarship. The Book of Tobit and Paul's First Letter to the Corinthians (1 Cor 8-10) are examined to demonstrate this the.